Mapuche Herbal Medicine Inhibits Blood Platelet Aggregation. (20th October 2011) - Falkenberg, Susan Skanderup; Tarnow, Inge; Guzman, Alfonso; Mølgaard, Per; Simonsen, Henrik Toft
Abstract : 12 plant species traditionally used by the Mapuche people in Chile to treat wounds and inflammations have been evaluated for their direct blood platelet inhibition. Seven of the 12 tested plant species showed platelet inhibitory effect in sheep blood, and four of these were also able to inhibit the ADP- (5.0 μ M) and collagen- (2.0 μ g/mL) induced aggregations in human blood. These four species in respective extracts (in brackets) were Blechnum chilense (MeOH), Luma apiculata (H2 O), Amomyrtus luma (DCM : MeOH 1 : 1) and Cestrum parqui (DCM : MeOH 1 : 1). The platelet aggregating inhibitory effects of A. luma (DCM : MeOH 1 : 1), and L. apiculata (H2 O) were substantial and confirmed by inhibition of platelet surface activation markers.